2021
DOI: 10.1002/hsr2.377
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary and non‐voluntary blood donations among doctors

Abstract: Background Physicians may be an important source of blood donations as they are more likely to be familiar with the importance of donating and the donation process. The aim of this study is to report physicians' knowledge, attitudes, and practices towards voluntary and non‐voluntary blood donations. Study Design and Methods This was a cross‐sectional study conducted at King Faisal Specialist Hospital and Research Centre (KFSH&RC), Saudi Arabia. One‐hundred‐and‐sixteen physicians and dentists responded to an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…This reluctance towards financial incentives paralleled the attitude observed among Saudi students. [15] However, another study identified nutritional and medical factors as the primary obstacles to voluntary donation, [16] highlighting their significance as key barriers in this context.…”
Section: Discussionmentioning
confidence: 99%
“…This reluctance towards financial incentives paralleled the attitude observed among Saudi students. [15] However, another study identified nutritional and medical factors as the primary obstacles to voluntary donation, [16] highlighting their significance as key barriers in this context.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that there was a significant relationship between the educational level of the participants and the responses of those with infectious diseases, those using medication, and those using aspirin. Saleh et al similarly found that factors preventing individuals from donating blood were the donor's medical conditions and nutritional deficiencies [20]. Oh et al found in their study that people using low doses of aspirin (81 mg) could donate blood as long as their coagulation status was not significantly impaired [21].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, determining the reasons for donor deferral will lead to a higher rate of donor return and retention. For donors who have been placed on a temporary hold, greater accessibility and more frequent invites are essential [19,59,60]. In addition, cultural, educational, and socioeconomic inequalities may explain some of the observed similarities and discrepancies among the most prevalent reasons for blood donor rejection.…”
Section: Discussionmentioning
confidence: 99%